Analysis of Potassium Ion (K+), Sodium Ion (Na+), and Proteins from Coconut Water Variety of Coconut and Hybrid Coconut - Sagir Alva (Journal of Chemical Natural Resources, 2021)
Analysis of potassium ion (K+), sodium ion (Na+), and proteins of Dalam coconut varieties water and Hybrid coconut varieties water have been done. The sample is green coconut which was taken simple random from Deli Tua Barat village in the regency of Deli Tua. Analysis of potassium ion (K+) and sodium ion (Na+) was determined by Atomic Absorption Spectrophotometry method (AAS) and analysis of protein was determined by the Kjeldahl method. From the result analysis of Dalam coconut varieties water contain amount potassium ion 321.60 mg/100 mL + 0,77 mg/100 mL, sodium ion 33.17 mg/100 mL + 1.85 mg/100 mL, and protein 0,18 % + 0.05 %. Whereas Hybrid coconut varieties water contain amount potassium ion 278.67 mg/100 mL + 1.53 mg/100 mL, sodium ion 31.33 mg/100 mL + 0.83 mg/100 mL, and protein 0.48 % + 0.3 %.